COMPONENTS OF THE WAY OF LIFE OF PEDAGOGICAL WORKERS AT THE STAGE OF PROFESSIONAL TRAINING DURING MARTIAL LAW - Латіна, Ганна (SWorldJournal, 2024)
In order to assess the lifestyle components of pedagogical workers at the stage of professional training during martial law, risk factors for the development of non-infectious diseases were assessed in 178 pedagogical workers at the stage of professional